L’activité des médiatrices interculturelles en contexte médical : un rempart aux injustices épistémiques ? - Marwa Mahmoud; Nathalie Muller-Mirza (Éducation et Socialisation)
Through this paper, we explore plurilingual and intercultural communication’s situations in a medical context from the point of view of epistemic injustices (Fricker, 2007). Using narrative-explicitative interviews on two situations (concerning birth and death), described by two intercultural mediators, we analyze their practices and highlight what they do to ensure that non-native speakers’ voice is listened to and believed. Our study contributes, on the one hand, to highlighting certain aspects related to epistemic injustices in intercultural communication, and on the other hand, to rethinking critically the relations between the ontologies underlying the relationship to the other, to the body and to health, mobilized in medical institutions.